The Cambridge companion to English literature, 1500-1600. - Kinney, Arthur F. (Cambridge : New York : Cambridge University Press, 2000)
This is the first comprehensive account of English Renaissance literature in the context of the culture which shaped it: the courts of Henry VIII, Edward VI, Mary and Elizabeth I, the tumult of Catholic and Protestant alliances during and following the Reformation, the development of humanism, the age of printing and of New World discovery."--Back cover.
Includes notes and index.
Keywords: English literature -- Early modern, -- History and criticism. -- 1500-1700; Literature and history -- Great Britain -- History -- 16th century